Archaeology on the Apulian-Lucanian border - Small, Alastair, (Archaeopress Archaeology, 2022)
The broad valley of the Bradano river and its tributary, the Basentello, separates the Apennine mountains in Lucania from the limestone plateau of the Murge in Apulia in southeast Italy. This book explains how the pattern of settlement and land use changed in the valley over the whole period from the Neolithic to the late medieval.